2013
DOI: 10.1002/star.201300034
|View full text |Cite
|
Sign up to set email alerts
|

Association between allelic variation at theWaxylocus and starch physicochemical properties using single-segment substitution lines in rice (Oryza sativaL.)

Abstract: The Waxy locus is the major locus controlling AM synthesis in rice endosperm. . Through Waxy genotype association analysis, functions of the four Waxy nucleotide polymorphisms on rice starch properties were determined. Analysis of correlation among the cooking and pasting parameters indicated that most of the traits were significantly correlated. The present results have important implications for rice breeders to select favorite Waxy alleles in rice grain quality improvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
25
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 25 publications
3
25
1
Order By: Relevance
“…Correlation analysis was conducted to characterize the relationships between activities of key starch synthesis enzymes, amylopectin chain length distribution, AAC, GC, GT, and pasting viscosity parameters. The data of starch cooking and pasting parameters used for correlation calculations was cited from Teng et al (2013).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Correlation analysis was conducted to characterize the relationships between activities of key starch synthesis enzymes, amylopectin chain length distribution, AAC, GC, GT, and pasting viscosity parameters. The data of starch cooking and pasting parameters used for correlation calculations was cited from Teng et al (2013).…”
Section: Discussionmentioning
confidence: 99%
“…So far, at least five common Wx alleles including wx, Wx t , Wx g1 , Wx g2 and Wx g3 have been identified (Teng et al 2012). Recently, further comparison studies have revealed that each of the five Wx alleles has its unique function on rice cooking and pasting properties (Teng et al 2013). However, apart from AAC, exact physiological and starch structural mechanisms of how the Wx allelic variation affects starch properties has not been clearly reported.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations